Volume 1: Compressors, Fans and Pumps; Turbines; Heat Transfer; Combustion, Fuels and Emissions 2017
DOI: 10.1115/gtindia2017-4686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotor Tip Winglet on the Performance and Stability of a Transonic Axial Compressor

Abstract: Winglets are plane surfaces with certain thickness and different shapes. Winglets are used in aircraft to reduce wing tip vortex which is created due to differential pressure in between pressure surface and suction surface. In transonic axial compressor, rotor tip leakage vortex interaction with shock layer and shroud boundary layer leads to total pressure loss and initiation of stall phenomenon. Effect of tip winglets are investigated in compressor rotor cascade. Cascade investigation shows that rotor tip win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Niu et al 23 illustrated that the pressure side winglet can greatly expand the compressor stability margin. Varpe et al 24 revealed the influence of pressure and suction side winglet in a transonic rotor, and confirmed the most substantial improvement caused by the suction side winglet.…”
Section: Introductionmentioning
confidence: 88%
“…Niu et al 23 illustrated that the pressure side winglet can greatly expand the compressor stability margin. Varpe et al 24 revealed the influence of pressure and suction side winglet in a transonic rotor, and confirmed the most substantial improvement caused by the suction side winglet.…”
Section: Introductionmentioning
confidence: 88%
“…By changing the structure of the casing or blades, they reallocate the flow rate and blade loading in the tip region and extend the operating range of compressors. Typical passive flow control methods include casing treatment [2][3][4], blade tip winglets [5,6], and vortex generators [7,8]. However, passive control methods will inevitably cause a significant penalty in the efficiency and the pressure ratio [9].…”
Section: Introductionmentioning
confidence: 99%
“…Stockhaus et al [6] found that PSS helps to reduce tip leakage flow. It should be noted that tip squealer geometry is very different with blade winglet [17,18], although both are targeted to control tip clearance flow.…”
Section: Introductionmentioning
confidence: 99%